Impact of Anti-Type 2 Inflammation Biologic Therapy on COVID-19 Clinical Course and Outcome - Poddighe D; Kovzel E (Dove Medical Press, 2021)
Dimitri Poddighe,1,2 Elena Kovzel2 1Department of Medicine, Nazarbayev University School of Medicine, Nur-Sultan, 010000, Kazakhstan; 2Clinical Academic Department of Pediatrics, University Medical Center (UMC), Nur-Sultan, 010000, KazakhstanCorrespondence: Dimitri Poddighe Email dimitri.poddighe@nu.edu.kzAbstract: SARS-CoV-2 pandemic had a general and deep impact on the clinical management of chronic diseases, including respiratory and allergic disorders. At the beginning of the pandemic, one of the main concerns was the potential impact of immunosuppressive/immunomodulatory drugs on COVID-19 clinical course. In this review, we aim to summarize and analyze the available clinical evidence from patients treated with anti-type 2 inflammation biologics (including anti-IgE, anti-IL-5 and anti-IL-4 agents), who developed COVID-19. Overall, the treatment with anti-Th2 biologics can be considered safe during COVID-19. It does not worsen the clinical course and outcome of COVID-19, and it may be actually protective somehow from developing severe forms. Moreover, patients treated with these biological agents do not seem to be more prone to get infected by SARS-CoV-2.Keywords: COVID-19, SARS-CoV-2, omalizumab, dupilumab, benralizumab, mepolizumab, reslizumab, asthma, chronic spontaneous urticaria, biologics